FENOMENA PERNIKAHAN MAHASISWA DAN DAMPAKNYA DALAM AKTIVITAS BELAJAR DI UNIVERSITAS PENDIDIKAN INDONESIA - Dwita Maharani, - (2020)
The reason the researchers chose students as the object of this research was because they saw the number of students marrying before completing their studies, so that it made researchers feel interested and curious about whether these married students could increase their learning activities or vice versa. The hope that arises is that students will be able to respond positively to these demands by making adjustments to various external demands without overriding the demands within themselves. In this study, it was reviewed through the Social Action Theory which was coined by Max Weber to see the behavior and actions of married students towards both academic and non-academic learning activities. This study uses a qualitative approach with descriptive study methods. Researchers took the key informants of 5 student participants from the 2016 class who were still active as students because the average student married during the 5/6 semester in college and 2 parents and 5 classmates / close relatives of the participants became supporting informants. The purpose of this study was to determine the phenomenon of student marriage and the impact on learning activities during lectures. The results showed: (1) the main factors of students getting married, namely religious factors and support from the closest people who convinced students to get married; (2) Student motivation in learning activities is due to the awareness of the importance of education to improve self quality so as to spur students to study hard to graduate on time and pursue their goals; (3) Students who are married will have multiple different roles simultaneously and be responsible for these roles so that they can be fulfilled; (4) The multi-role impact on learning activities is that it is difficult to divide time between taking care of household and college assignments.